Implementasi Pendidikan Karakter Berbasis Budaya Sekolah Unggul di SD Muhammadiyah Plus dan SD Islam Al-Azahar 22 Kota Salatiga - Husein, Afif; Sa’adi, Sa’adi; Khamid, Abdul (CV. Creative Tugu Pena, 2022)
This article aims to identify school policies that influence students' character through excellent cchool culture, to identify strategies for instilling building character values through excellent school culture, and to identify supporting and inhibiting factors in the implementation of excellent school culture-based character building. This article used qualitative method. The result showed that (1) School cultural policies at SD Muhammadiyah Plus that include character building values, such as good public relations (5S culture), morning assembly, student appointments, dhuha prayer, dhuhur prayer together. Meanwhile, at Al-Azhar Islamic Elementary School 22 Salatiga, flag ceremony, pledge, Ramadhan boarding school, dhuhur prayer together, tahfidz, and humanism. (2) SD Muhammadiyah Plus Salatiga employs a strategy that includes a teacher acting as an example, making slogans or yelling, continuous supervision of students, and providing positive examples. Meanwhile, SD Islam Al-Azhar 22 Salatiga city uses a unique strategy: implementing the adab curriculum, setting an example for students, rewarding good behavior, creating pearls or slogans, monitoring through parents or peers, and becoming accustomed to good behavior in the classroom. (3) The similarity of objectives, human resources, and stakeholders are superior supporting factors for implementing school culture-based character building at SD Muhammadiyah Plus Salatiga. Infrastructure and stakeholders are supporting factors for SD Islam Al-Azhar 22 Salatiga. Meanwhile, at SD Muhammadiyah Plus, the inhibiting factors are students' parents, motivation, and the environment. And for the 22 Al-Azhar Islamic Elementary School in Salatiga, namely the external environment and the parents of students. Keywords: Development Learning Media, Learning Media Proshow, Learning Indonesia Language